Catalytic Enantioselective Synthesis of N, Cα, Cα‐Trisubstituted α‐Amino Acid Derivatives Using 1H‐Imidazol‐4(5H)‐ones as Key Templates1. (23rd April 2015) - Etxabe, Julen; Izquierdo, Joseba; Landa, Aitor; Oiarbide, Mikel; Palomo, Claudio
Abstract: 1 H ‐Imidazol‐4(5 H )‐ones are introduced as novel nucleophilic α‐amino acid equivalents in asymmetric synthesis. These compounds not only allow highly efficient construction of tetrasubstituted stereogenic centers, but unlike hitherto known templates, provide direct access to N‐substituted (alkyl, allyl, aryl) α‐amino acid derivatives.